DOI: 10.11606/t.61.2010.tde-02122010-151726
|View full text |Cite
|
Sign up to set email alerts
|

Achados audiológicos de indivíduos com a síndrome G/BBB

Abstract: Agradecimentos AGRADECIMENTOSAgradeço a Deus pela constante presença em minha vida, orientando meus passos e abençoando minhas decisões. Ao Prof. Dr. José Alberto de Souza Freitas, Superintendente do Hospital de Reabilitação de Anomalias Craniofaciais-USP. Ao Prof. Dr. Neivo Luiz Zorzetto, meu querido orientador, exemplo de competência profissional. Agradeço pelo incentivo e confiança demonstrados na orientação de mais este trabalho. Ao Dr. Antonio Richieri-Costa, chefe e amigo, exemplo de dedicação à ciência,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Pro(4-OH) was once thought to be unique to collagen and elastin (Eastoe, 1967). However, recent evidence has suggested that this hydroxylated unique amino acid is a structural component of the 4-hydroxyproline-rich glycoproteins found in the extracellular matrices of primary cell wall of plants (angiosperm) (Lamport, 1980;Fincher et al, 1983;McNeil et al, 1984;Cooper et al, 1987;Cassab and Varner, 1988) and seeds including the cell walls of soybean seed coats (Cassab et al, 1985;Cassab andVarner, 1987,1988), developing soybean tissue (Ye and Varner, 1991), and the cell walls of wounded and 0 Mean values and standard error of measurements (SEM) for three replicates and 48 determinations. Significance: F, values from analysis of variance between treatments; *, P < 0.05; ns, not significant; C V, coefficient of variation.6 Calculated according to the method of Heidelbaugh et al (1975).c The total protein, WE, and CF constants were calculated according to the method of Horstmann (1979), where CF is the apparent average residue molecular weight increased in proportion to the missing tryptophan and cyst(e)ine values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pro(4-OH) was once thought to be unique to collagen and elastin (Eastoe, 1967). However, recent evidence has suggested that this hydroxylated unique amino acid is a structural component of the 4-hydroxyproline-rich glycoproteins found in the extracellular matrices of primary cell wall of plants (angiosperm) (Lamport, 1980;Fincher et al, 1983;McNeil et al, 1984;Cooper et al, 1987;Cassab and Varner, 1988) and seeds including the cell walls of soybean seed coats (Cassab et al, 1985;Cassab andVarner, 1987,1988), developing soybean tissue (Ye and Varner, 1991), and the cell walls of wounded and 0 Mean values and standard error of measurements (SEM) for three replicates and 48 determinations. Significance: F, values from analysis of variance between treatments; *, P < 0.05; ns, not significant; C V, coefficient of variation.6 Calculated according to the method of Heidelbaugh et al (1975).c The total protein, WE, and CF constants were calculated according to the method of Horstmann (1979), where CF is the apparent average residue molecular weight increased in proportion to the missing tryptophan and cyst(e)ine values.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of plants to adapt to low temperatures has been attributed to changes in specific biochemical processes (Caldwell, 1990), including the synthesis of temperature-shock proteins (Guy et al, 1985), alterations in structure and function of enzymes involved in key metabolic reactions (Berry and Bjorkman, 1980 Pierce, 1988), and the development and repair of the photosynthetic apparatus (Goldberg et al, 1989; Nie and Baker, 1991). Changes in cell plasma membrane structure (Steponkus, 1984; Steponkus and Lynch, 1989; Raison and Orr, 1990) or in the insoluble cell wall proteins may also be involved in plant cell acclimation to temperature extremes (Lamport, 1977(Lamport, ,1980Cassab andVarner, 1987, 1988). The work of Lamport (1977of Lamport ( ,1980 demonstrated that the extracellular matrices of the primary cell walls of angiosperms comprise 4-hydroxyproline-rich glycoproteins, i.e., extensins, arabinogalactan proteins, salt-extractable glycoproteins, lectins, and agglutinins, in which a number of proline residues are posttranslationally modified to 4-trans-hydroxyproline (Lamport, 1980;Fincher et al, 1983;McNeil et al, 1984;Cassab et al, 1985; Cooper et al, 1987;Corbin et al, 1987;Averyart-Fullard et al, 1988; Showalter et al, 1990; Marcus et al, 1991;Kielszewskietal., 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization estimates that about 6-7 million people are infected worldwide, primarily in Latin America, where the disease is endemic (WHO, 2018). Bolivia has the highest CD incidence in the world (Organizació n Panamericana de la Salud, 2006;WHO, 2015), and T. cruzi infection has a high prevalence in different rural areas, primarily affecting the indigenous communities in the inter-Andean valleys and the Chaco (Cassab et al, 1999; Organizació n Panamericana de la Salud, 2006;de Araú jo-Jorge and Medrano-Mercado, 2009). CD presents two clinical phases.…”
Section: Introductionmentioning
confidence: 99%